Spiritualitas dan Kompensasi dalam Meningkatkan Produktivitas Guru Madrasah: Studi di Konteks Sosial-Keagamaan Tana Toraja - Tanal, Ali Nahruddin; Junita; Suryani, Lilis (POROS ONIM: Jurnal Sosial Keagamaan, 2024)
This study emphasizes spirituality and compensation in improving madrasah teacher productivity in Tana Toraja, a region with strong religious traditions. This study seeks to understand (1) the impact of spirituality on teacher performance and (2) the impact of compensation on teacher productivity in Tana Toraja. This study used ex post facto quantitative methods in a Kabupaten Tana Toraja madrasah. Select 51 teachers from 104 using proportional stratified random sampling. SPSS is used for simple regression analysis of kuesioner data. Spirituality positively affects madrasah teacher productivity by 21,9%, whereas compensation positively affects it by 35,5%. This shows that spirituality and compensation can significantly improve madrasah teacher productivity. This study contributes to multicultural religious education by showing the importance of spirituality and compensation on teacher productivity and social harmony in Tana Toraja.